THE WAYS OF TEACHING FOREIGN LANGUAGES TO DISABLED CHILDREN - Hamroqulova Maftuna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article provides information about the reasons and strategies how to educate children who are disabled. In addition to this, exactly what methods are utilized and their results are also discussed. First of all, we should answer the question of why these children ought to be taught. In today's innovative world, students with inabilities face significantly increasing rates of violence and restraint in schools. As a result of this, the disabled children have numerous issues.